Comparative efficacy of 5 sodium-glucose cotransporter protein-2 (SGLT-2) inhibitor and 4 glucagon-like peptide-1 (GLP-1) receptor agonist drugs in non-alcoholic fatty liver disease: A GRADE-assessed systematic review and network meta-analysis of randomized controlled trials - Gu, Yunpeng; Sun, Lei; Zhang, Wei; Kong, Tingting; Zhou, Run; He, Yining; Deng, Chaohua; Yang, Luping; Kong, Jianing; Chen, Yutong; Shi, Junping; Hu, Yanli (Frontiers in Pharmacology, 2023)
Background: The relative efficacy of 5 sodium-glucose cotransporter protein-2 (SGLT-2) inhibitors and 4 glucagon-like peptide-1 (GLP-1) receptor agonists for non-alcoholic fatty liver disease (NAFLD) therapy has not been sufficiently investigated. Methods: Randomized controlled trials (RCTs) in which patients with NAFLD were treated with SGLT-2 inhibitors or GLP-1 receptor agonists were included. Primary outcomes were improvements in liver enzymes and liver fat parameters, while secondary outcomes included anthropometric measures, blood lipids and glycemic parameters. The frequentist method was used to perform a network meta-analysis. Evidence certainty was assessed using the grading of recommendations assessment, development, and evaluation (GRADE). Results: The criteria were satisfied by 37 RCTs with 9 interventions (5 SGLT-2 inhibitors and 4 GLP-1 receptor agonists). Based on high certainty evidence, in patients with NAFLD (or comorbid with type 2 diabetes), semaglutide could lower alanine aminotransferase as well as aspartate aminotransferase, γ-glutamyl transferase, controlled attenuation parameter, liver stiffness measurement, body weight, systolic blood pressure, triglycerides, high-density lipoprotein-cholesterol, glycosylated hemoglobin. Liraglutide could lower alanine aminotransferase as well as subcutaneous adipose tissue, body mass index, fasting blood glucose, glycosylated hemoglobin, glucose and homeostasis model assessment, while dapagliflozin could lower alanine aminotransferase as well as body weight, fasting blood glucose, postprandial blood glucose, glycosylated hemoglobin, glucose and homeostasis model assessment. Conclusion: Semaglutide, liraglutide, and dapagliflozin all have a certain effect on NAFLD (or comorbid with type 2 diabetes) based on high confidence evidence from indirect comparisons, and semaglutide appears to have a therapeutic advantage over the other included medicines. Head-to-head studies are needed to provide more confidence in clinical decision-making.